Analysis of the Effect of the Number of Tourist Visits, Tourist Attractions, and Hotels/Lodging on the Local Income of Gresik Regency - Anggraini, Natania; Marseto; Fitria Utami, Anisa (International Journal of Economics, Business and Innovation Research, 2026)
Regional Original Income (PAD) is one of the main indicators of regional fiscal independence in the era of regional autonomy. The tourism sector has strategic potential in increasing PAD through the economic activities generated. This study aims to analyze the influence of the number of tourist visits, the number of tourist attractions, and the number of hotels/lodgings on the Regional Original Income of Gresik Regency. The study uses a quantitative approach with a multiple linear regression analysis method. The data used is annual secondary data for the period 2010–2024 obtained from related agencies. The results of the study indicate that simultaneously the variables of the number of tourist visits, the number of tourist attractions, and the number of hotels/lodgings influence the Regional Original Income of Gresik Regency. This finding indicates that the tourism sector has a significant role in supporting the increase in regional revenue. Therefore, integrated and sustainable tourism development needs to be continuously improved to strengthen regional fiscal independence.